IDENTIFIKASI HAMBATAN IMPLEMENTASI PEMBELAJARAN TEMATIK PADA GURU KELAS RENDAH DI SDN 02 MUJUR LOMBOK TENGAH - Nurul Khaerina Khazni; Nurul Kemala Dewi; Awal N. K. Rosyidah (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2021)
This study aims to determine the Identification of Barriers to Thematic Learning Implementation in Low Grade Teachers at SDN 02 Mujur, Academic Year 2020/2021. This type of research is descriptive qualitative. The subjects of this study were the principal, teachers in grades I, II, and III of SD Negri 02 Mujur. Data collection techniques were carried out through interviews and documentation. The results showed that there were differences in the barriers experienced by teachers in implementing thematic learning in low classes before and after the Covid-19 Pandemic. Before the Covid-19 Pandemic, the obstacles experienced by teachers were the lack of teacher knowledge about thematic learning, teachers had difficulty understanding what components must be in thematic lesson plans, lack of facilities and infrastructure that supported learning such as teaching aids, teachers had difficulty implementing activities 5M in low classes, lack of enthusiasm from students in grades II and III in participating in thematic learning and teachers find it difficult to provide assessments to students using K13 assessments. Teachers' obstacles to implementing thematic learning after the Covid-19 Pandemic were teachers having difficulty teaching from one village to another because of the distance between remote villages, the absence of facilities for teaching such as blackboards, markers, and erasers, many students were absent from following learning and teachers cannot provide maximum assessment to students due to limited face-to-face time between students and teachers while studying in the midst of the Covid-19 Pandemic